Characterization of the phenotypes of methicillin- and vancomycin-susceptible Staphylococcus argenteus after vancomycin passages. (December 2022) - Chang, Chih-Hsiang; Lee, Sheng-Hsun; Lin, Yu-Chih; Hsu, Chih-Yun; Cheng, Chih-Chieh; Teng, Shih-Hua; Chen, Mei-Feng; Hsieh, Pang-Hsin; Chang, Yuhan; Chiang-Ni, Chuan
Highlights: Staphylococcus argenteus is able to develop vancomycin-intermediate phenotypes. S. argenteus could convert to strong biofilm producers after vancomycin treatments. An increase of ica expression was observed in the strong biofilm producers. Adapting vancomycin and converting to biofilm producers could be related to treatment failure. ABSTRACT: Objectives: Staphylococcus argenteus is generally more susceptible to antibiotic treatments than Staphylococcus aureus ; however, the study showed that the daptomycin/vancomycin-resistant S. argenteus was isolated from a patient with repeated antibiotic treatments. In this study, the methicillin- and vancomycin-susceptible S. argenteus isolates were used to characterize the phenotypes of S. argenteus after vancomycin passages in vitro. Methods: Eleven S. argenteus isolates were used for passaging under different concentrations of vancomycin. The minimal inhibitory concentration (MIC) of vancomycin was determined by the agar dilution assay, and the biofilm mass of the passaged variants was quantified by the crystal violet staining assay and observed under the confocal microscope. Results: The MIC of vancomycin for eight of 11 S. argenteus isolates was increased from ≤2 µg/mL to ≤4–8 µg/mL after vancomycin passages. Two variants with the high-level vancomycin-intermediate (vancomycin MIC ≤8 µg/mL) phenotype were identified, and the parental strains of these variants did not have the heterogeneous vancomycin-intermediate population determined by the population profile analysis. Further, three S. argenteus isolates showed an increase in biofilm production and icaA transcription after the low-dose (2 µg/mL) vancomycin passages. Conclusions: S. argenteus is capable of acquiring a vancomycin-tolerant phenotype and/or converting to a strong biofilm producer after vancomycin passages, which could contribute to the decrease of their antibiotic susceptibility.